Guide to cloud computing : principles and practice - Hill, Richard (Computer communications and networks, 2013)
This book describes the landscape of cloud computing from first principles, progressing step-by-step through the process of building and configuring a cloud environment. Includes review questions, hands-on exercises, study activities and discussion topics